Socio-Economic Network of Cattle Business in the Animal Market of Lili - Camplong, Kupang Regency - Jehamat, Lasarus; Jelahut, Yosef Emanuel; Meka, Christine E.; Saldanah Neno, Marianus; Jelahut, Felisianus E. (PT. Riset Press International, 2023)
There are four fundamental goals for the people of East Nusa Tenggara in raising and developing cattle as a legacy from the Colonial. First, the cow is a sign of social status. The social status of the local community is not solely determined by how much money a family has, but more than that, social status is also determined by how many cows are kept in a large paddock. Secondly, the cow is an animal that supports the mating process. The cow is an animal that is a symbol of marriage for the people of NTT. Third, cows as animals that help the economy. Fourth, cattle are a commodity that is traded by local economic authorities who have extensive business networks. This descriptive qualitative research aims to examine the socio-economic networks among cattle farmers who come from the lower classes who also work as subsistence farmers, concerning cattle businessmen. As qualitative research, this study used three main methods to obtain field data. First, the in-depth interview was conducted with buyers, the local strong man Business Network, and the government of Kupang Regency. The second is the observation which was done in several villages in Kupang Regency and Camplong Market. Third, focus group discussion (FGD) was carried out on various related parties in the selling cycle involving local governments, businesses, cattle traders, and the community in general. The results of this study will be published in scientific journals and local media